Correlation of Hypoxic Ischemic Encephalopathy Stages with Clinical Variables - Manchala Chandra Sekhar (Asian Journal of Clinical Pediatrics and Neonatology, 2020)
Background: Injury to the CNS related with perinatal asphyxia is referred to as Hypoxic-Ischemic Encephalopathy which is the utmost severe neurological condition that arises in perinatal periods. The aim is to assess clinical variables with hypoxic-ischemic encephalopathy stages. Subjects and Methods: A clinical study of 42 new borns asphyxiated were assessed clinically of these asphyxiated neonates was carried out using Sarnath and Sarnath Staging of HIE. The association between asphyxia at birth and HIE has been examined. Results: In the present study, maternal history, gestational age, and mode of delivery were found to be not significant and do not correlate with the severity of HIE. Sarnath and Sarnath clinical scoring for neurobehavioral signs and symptoms 13 (31%) had reveal of HIE stage -1, 14 (33%) are of stage -2 and severe HIE (HIE-III) common, seen in 15cases (36%). The correlation of non-stress test (NST), Meconium staining was more in stage-3 in HIE stages and statistically significant. Conclusion: During the diagnosis and treatment of HIE patients, analysis of clinical variables will improve the objectivity of newborn assessment and evaluation and early start of care.